The E2F3/miR-125a/DKK3 regulatory axis promotes the development and progression of gastric cancer - Pei, Yihua (Cancer Cell Int, 2019)
BACKGROUND: Gastric cancer (GC) is one of the most common malignant tumours with high mortality and metastasis rates. E2F3, miR-125a and DKK3 have been reported to be involved in various cancer types, but their detailed roles in GC have not been fully understood. METHODS: A QRT-PCR assay was used to examine the expression of E2F3, miR-125a and DKK3 in metastatic and nonmetastatic GC tissues. DKK3 plasmids, DKK3 shRNA, miR-125a mimic and miR-125a inhibitor were transfected into BGC823 cells to evaluate the biological functions of DKK3 and miR-125a. A scratch wound healing assay and Transwell assay were utilized to determine the migratory and invasive ability of BGC823 cells transfected with the DKK3 plasmids, DKK3 shRNA, miR-125a mimic and miR-125a inhibitor. Moreover, qRT-PCR and WB analysis were used to analyse the mRNA and protein expression levels of metastasis-related genes after proper transfection. The target relationship between miR-125a and the DKK3 mRNA 3′UTR was determined by a dual luciferase reporter assay, while the interaction between E2F3 and miR-125a was analysed by a ChIP assay. RESULTS: The clinical data showed that the DKK3 expression level in metastatic GC samples was significantly less than that in nonmetastatic GC samples, whereas the E2F3 and miR-125a expression levels in metastatic GC samples were notably greater than those in nonmetastatic GC samples. Moreover, knockdown of DKK3 and overexpression of miR-125a markedly promoted the migratory and invasive abilities of GC cells. Additionally, the protein and mRNA expression levels of metastasis-related genes, including N-cadherin, Vimentin, MMP2 and MMP9, were markedly decreased in the DKK3 and miR-125a inhibitor groups compared to their control groups and markedly increased in the DKK3 shRNA and miR-125a groups compared with the control group. Finally, a dual luciferase reporter assay and ChIP assay showed that E2F3 binds to the miR-125a promoter and that the DKK3 mRNA 3′UTR is a direct target of miR-125a. Furthermore, analysis of Kaplan–Meier curves also confirmed the regulatory role of E2F3 on miR-125a. Additionally, BGC823 cells transfected with E2F3 plasmids and shRNA downregulated and upregulated the expression of DKK3, respectively. CONCLUSION: Our results suggested that E2F3 might play a tumour-promoting role in the metastasis and progression of GC by regulating the miR-125a/DKK3 axis.